A framework for the design of privacy preserving pervasive health care - Moncrieff, Simon; Venkatesh, Svetha; West, Geoffrey (Institute of Electrical and Electronics Engineers, 2009)
Privacy is an important aspect of pervasive and ubiquitous computing systems, and, in particular, pervasive healthcare. With reference to previous approaches on developing privacy sensitive pervasive healthcare applications, we detail a framework for the design of such systems that aims to minimise the impact of privacy on such systems. In reviewing previous approaches, we extract and combine common elements in order to unify the approaches and create a more formal methodology for designing privacy mechanisms in pervasive healthcare applications. In doing so we also consider the mannerin which ubiquitous technologies impact on privacy and methods for reducing this impact. We demonstrate how the framework can be applied by using examples from the previousapproaches. In addressing privacy issues, the framework aims to remove a large obstacle to deployment of pervasive healthcare systems, acceptance of the technology.